Last visit was: 17 Jun 2024, 00:10 It is currently 17 Jun 2024, 00:10
Toolkit
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

# In the formula shown, if g is a constant and x = –6 when t = 2, what i

SORT BY:
Tags:
Show Tags
Hide Tags
Senior Manager
Joined: 04 Sep 2017
Posts: 325
Own Kudos [?]: 20314 [15]
Given Kudos: 50
Retired Moderator
Joined: 19 Oct 2018
Posts: 1870
Own Kudos [?]: 6509 [1]
Given Kudos: 705
Location: India
GMAT Club Legend
Joined: 12 Sep 2015
Posts: 6814
Own Kudos [?]: 30567 [4]
Given Kudos: 799
Director
Joined: 14 Jul 2010
Status:No dream is too large, no dreamer is too small
Posts: 966
Own Kudos [?]: 4990 [0]
Given Kudos: 690
Concentration: Accounting
Re: In the formula shown, if g is a constant and x = –6 when t = 2, what i [#permalink]
Top Contributor
gmatt1476 wrote:
$$x = \frac{1}{6}gt^2$$
In the formula shown, if g is a constant and x = –6 when t = 2, what is the value of x when t = 4 ?

A. –24
B. –20
C. –15
D.  20
E.  24

We need to get the constant (g) first; $$x = \frac{1}{6}gt^2$$; $$-6 = \frac{1}{6}g2^2$$ $$= -6 = \frac{1}{6}4g$$; $$g=-9$$

Now putting $$g=-9$$ in the original equation;$$x = \frac{1}{6}gt^2$$=$$x = \frac{1}{6}-9*4^2$$

$$=x = \frac{1}{6}-9*16$$

$$x=-24$$

The answer is $$A$$
Math Revolution GMAT Instructor
Joined: 16 Aug 2015
Posts: 10147
Own Kudos [?]: 16845 [0]
Given Kudos: 4
GMAT 1: 760 Q51 V42
GPA: 3.82
Re: In the formula shown, if g is a constant and x = –6 when t = 2, what i [#permalink]
x = $$\frac{1}{6} * g * t^2$$

=> g = $$\frac{(6x) }{ t^2}$$

=> g = $$\frac{(6 * -6) }{ (2^2)} = \frac{-36}{4} = -9$$

At t = 4:

=> x = $$\frac{1}{6} * (-9) * (4^2)$$

=> x = -24

Non-Human User
Joined: 09 Sep 2013
Posts: 33616
Own Kudos [?]: 838 [0]
Given Kudos: 0
Re: In the formula shown, if g is a constant and x = 6 when t = 2, what i [#permalink]
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
Re: In the formula shown, if g is a constant and x = 6 when t = 2, what i [#permalink]
Moderator:
Math Expert
93697 posts